PENGARUH ENDORPHINE MASSAGE TERHADAP INTENSITAS NYERI DISMINORE PADA SISWI SMP ISLAM AR-RAUDHOH DESA PASIR UTAMA - Andiyani, Sri; Andriana; Andriani, Rika (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2025)
Dysmenorrhea is defined as cyclic menstrual pain, which is accompanied by cramps, and can be accompanied by severe symptoms such as lower back pain, nausea, vomiting, diarrhea, headaches and even fainting. If dysmenorrhea occurs in teenagers, if it is not treated, it will have an impact on daily activity patterns, including not going to school or missing college, decreasing concentration and productivity and then causing a decrease in achievement. Efforts to reduce pain due to menstruation are a concern for women today. There are two types of therapy that can be used to treat dysmenorrhea, namely pharmacological therapy and non-pharmacological therapy. Endorphine Massage is an effective non-pharmacological way to reduce the intensity of pain during dysmenorrhea, namely by doing massage. This research aims to. determine the effect of endorphine massage on the intensity of dysmenorrhea pain in female students at Ar-Raudhoh Islamic Middle School, Pasir Utam Village. This research method is quantitative using the pre-experiment method with a one group pretest-posttest design approach. The sampling technique in this research is a purposive sampling technique where the samples used for research are those that meet certain criteria, namely 20 respondents. for data analysis using the T-Dependent statistical test, the p value = 0.000, thus, p-value (0.000) < 0.05 which indicates that there is an influence of Endorphine Massage to reduce the intensity of dysmenorrhea pain in Ar-Raudhoh Islamic Middle School Girls, Pasir Utama Village. . for female students to be able to do Endorphine Massage to reduce the intensity of dysmenorrhea pain